Lithium secondary battery, positive electrode active material, method for manufacturing same, and electric device
Patent Information
- Application Number
- CN202510413391.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]正极活性材料作为锂二次电池的重要组成部分,承担着提供锂离子的重要作用,在电池循环过程中,尤其是高电压下,正极活性材料与电解液的副反应加剧,使得含有其的锂二次电池的寿命衰减较快
Smart Images

Figure CN122930849A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of secondary batteries, specifically relating to a lithium secondary battery, a positive electrode active material and its preparation method, and an electrical device. Background Technology
[0002] Lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace and many other fields.
[0003] As an important component of lithium secondary batteries, positive electrode active materials play a crucial role in providing lithium ions. During battery cycling, especially under high voltage, the side reactions between the positive electrode active materials and the electrolyte intensify, resulting in a faster decline in the lifespan of lithium secondary batteries containing them. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a lithium secondary battery, which aims to improve the cycle life of lithium secondary batteries.
[0005] To achieve the above objectives, the first aspect of this application proposes a lithium secondary battery, comprising a positive electrode, an electrolyte, and a negative electrode. The positive electrode comprises a positive active material, which includes a bulk and a coating layer formed on at least a portion of the surface of the bulk. The coating layer comprises one or more elements selected from Si, P, S, B, F, Cu, Zn, Y, and Zr.
[0006] The surface of the positive electrode active material has n regions, where n is greater than or equal to 3. The standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.25%, and the average mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.4%.
[0007] This application includes at least the following beneficial effects: The lithium secondary battery of this application controls the standard deviation of the mass percentage of the coating element at different positions on the surface of the positive electrode active material, i.e., the coating layer, to be 0.1%-0.25%, and controls the average mass percentage of the coating element in n regions to be 0.1%-0.4%, so that the coating layer is uniformly coated on the body surface, which can effectively protect the positive electrode active material, thereby significantly improving the cycle life of the lithium secondary battery containing it.
[0008] In some embodiments, in a single region, the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element, and Zr element is 0.1%-1%. Accordingly, the cycle life of the lithium secondary battery can be improved.
[0009] In some embodiments, the main body comprises Li 1+x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, Li a Ni 0.5-x2 Mn 1.5- y2 M2 x2+y2 O4, LiMn 2-x3 M3 x3 O4, LiNi x4 Co y4 Mn z4 M4 (1-x4-y4-z4) O2, or one or more thereof, wherein M1 comprises one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, Q comprises one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, M2 comprises one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, 0.9≤a≤1.1, -0.2≤x2≤0.2, -0.02≤y2≤0.3, x2+y2≥0, 0<x3≤0.5, M3 comprises one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, 0<x4≤1, 0<y4≤1, 0≤z4<1, and M4 comprises one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr. Accordingly, the cycle life of the lithium secondary battery can be improved.
[0010] In some embodiments, the main body comprises Li 1+x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, wherein M1 comprises one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, and Q comprises one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr. Accordingly, the cycle life of the lithium secondary battery can be improved.
[0011] In a second aspect, this application proposes a positive electrode active material, the positive electrode active material comprising a body and a coating layer formed on at least a portion of the surface of the body, the coating layer comprising one or more of Si, P, S, B, F, Cu, Zn, Y, and Zr elements, the surface of the positive electrode active material having n regions, n being greater than or equal to 3, and the standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions being 0.1%-0.25%. Therefore, the positive electrode active material proposed in this application controls the standard deviation of the mass percentage of the coating elements at different positions on the surface of the positive electrode active material, i.e., the coating layer, to be 0.1%-0.25%, and the average mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in n regions to be 0.1%-0.4%, so that the coating layer is uniformly coated on the body surface, which can effectively protect the positive electrode active material and thus significantly improve the cycle life of lithium secondary batteries containing it.
[0012] In some implementations, the mass percentage of any one of the elements Si, P, S, B, F, Cu, Zn, Y, and Zr in a single region is 0.1%-1%. This can improve the cycle life of lithium secondary batteries.
[0013] In some embodiments, the thickness of the coating layer is 2nm-10nm. This can improve the cycle life of the lithium secondary battery.
[0014] In some embodiments, the body includes Li 1+x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, Li a Ni 0.5-x2 Mn 1.5-y2 M2 x2+y2 O4, LiMn 2-x3 M3 x3 O4, LiNi x4 Co y4 Mn z4 M4 (1-x4-y4-z4)one or more of O2, wherein M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, M2 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, 0.9≤a≤1.1, -0.2≤x2≤0.2, -0.02≤y2≤0.3, x2+y2≥0, 0<x3≤0.5, M3 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, 0<x4≤1, 0<y4≤1, 0≤z4<1, M4 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr. Accordingly, the cycle life of the lithium secondary battery can be improved.
[0015] In some embodiments, the main body comprises Li 1+x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, wherein M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr. Accordingly, the cycle life of the lithium secondary battery can be improved.
[0016] In a third aspect of the present application, the present application proposes a method for preparing a positive electrode active material, comprising: dissolving a soluble compound and a soluble polymer in water to form a solution, wherein the soluble compound includes one or more of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element, and Zr element; immersing the main body in the solution, and performing solid-liquid separation to obtain a solid; calcining the solid in an oxygen-containing atmosphere to obtain the positive electrode active material. Accordingly, by adding the soluble polymer during the preparation process of the coating layer, the disordered growth of the soluble compound crystals on the surface of the main body is inhibited, and the formation of island-shaped coatings is reduced, so that the coating layer is uniformly coated on the surface of the main body, which can effectively protect the positive electrode active material, thereby significantly improving the cycle life of the lithium secondary battery containing the same.
[0017] In some embodiments, the soluble compound includes one or more of the following: Na₂SiO₃, Li₂SiO₃, K₂SiO₃, H₄SiO₄, LiH₂PO₃, NaH₂PO₃, KH₂PO₃, Li₂HPO₃, Na₂HPO₃, K₂HPO₃, (NH₄)₃PO₄, NaF, KF, NH₄F, NaBF₄, H₂SiF₆, Na₂SO₄, K₂SO₄, (NH₄)₂SO₄, Na₂SO₃, K₂SO₃, Na₂S₂O₃, Li₂B₄O₇, Li₂B₄O₇·10H₂O, H₂BO₃, CuSO₄, Cu(NO₃)₂, ZnSO₄, Zn(NO₃)₂, Y(NO₃)₂, YCl₃, and Zr(SO₄)₂. This can improve the cycle life of lithium-ion secondary batteries.
[0018] In some embodiments, the soluble polymer has an average molecular weight of 500-100,000. This can improve the cycle life of lithium-ion batteries.
[0019] In some embodiments, the soluble polymer includes one or more of polyacrylic acid, sodium polyacrylate, polymethacrylic acid, polyethyleneimine, polyacrylamide, polyvinyl alcohol, polymethylacrylamide, polyallylamine, polydiallylamine, polyethylene glycol, polyvinyl acetate, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, and sodium chondroitin sulfate A. This can improve the cycle life of lithium secondary batteries.
[0020] In some embodiments, the mass ratio of the soluble compound, the soluble polymer, and water is (1-100):(1-30):100. This can improve the cycle life of the lithium secondary battery.
[0021] In some embodiments, the soaking time is 5-30 minutes. This can improve the cycle life of the lithium secondary battery.
[0022] In some embodiments, the solid-liquid separation includes one or more of centrifugation, vacuum filtration, and pressure filtration. This can improve the cycle life of lithium-ion batteries.
[0023] In some embodiments, the calcination temperature is 400°C-700°C. This can improve the cycle life of the lithium secondary battery.
[0024] In a fourth aspect of this application, an electrical device is proposed, comprising the lithium secondary battery described in the first aspect of this application.
[0025] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0026] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0027] Figure 1 This is a schematic diagram of a battery according to one embodiment of this application.
[0028] Figure 2 yes Figure 1 An exploded view of a battery according to one embodiment of this application is shown.
[0029] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0030] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0031] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0032] Figure 6 This is a schematic diagram of an electrical device in which a battery is used as a power source according to one embodiment of this application.
[0033] Figure 7 These are the SEM and EDS images of the positive electrode active material of Comparative Example 1 of this application.
[0034] Figure 8 This is a SEM image of the positive electrode active material of Comparative Example 1 of this application.
[0035] Figure 9 This is a SEM and EDS image of one location of the positive electrode active material of Comparative Example 2 of this application.
[0036] Figure 10 This is a SEM and EDS image of another location of the positive electrode active material in Comparative Example 2 of this application.
[0037] Figure 11 These are SEM and EDS images of the positive electrode active material of Example 1 of this application.
[0038] Figure 12 This is a SEM image of the positive electrode active material of Example 1 of this application.
[0039] Figure 13 These are SEM and EDS images of the positive electrode active material of Example 2 of this application.
[0040] Figure 14 This is a SEM image of the positive electrode active material of Example 2 of this application.
[0041] Figure 15 This is a comparison chart of the high-temperature storage performance of lithium secondary batteries in Examples 1, 2, 1, and 2 of this application.
[0042] Explanation of reference numerals in the attached figures:
[0043] 1. Battery cell; 11. Housing; 12. Electrode assembly; 13. Cover plate; 2. Battery module; 3. Battery pack; 31. Upper casing; 32. Lower casing. Detailed Implementation
[0044] The embodiments of the technical solution of this application are described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.
[0045] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0046] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0047] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0048] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0049] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0050] Currently, judging from market trends, the application of rechargeable batteries is becoming increasingly widespread. Rechargeable batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace, among other fields.
[0051] As a crucial component of lithium-ion rechargeable batteries, the positive electrode active material plays a vital role in providing lithium ions. During battery cycling, especially at high voltages, the side reactions between the positive electrode active material and the electrolyte intensify, leading to a faster decline in the lifespan of lithium-ion rechargeable batteries containing it. Taking lithium-rich layered oxides as an example, their poor lifespan is due to the oxidation of the electrolyte solvent on the surface of the positive electrode active material. The resulting interface layer (CEI) is unstable, and the electrolyte continues to oxidize. Simultaneously, electrolyte oxidation products shuttle to the negative electrode to oxidize the active lithium. The rapid and continuous consumption of active lithium and electrolyte causes a loss of the storage cycle capacity of the lithium-ion rechargeable battery, affecting its lifespan.
[0052] To reduce side reactions between the positive electrode active material and the electrolyte, a coating layer can be prepared on the surface of the positive electrode active material to isolate the electrolyte from contact with the positive electrode active material. However, the existing coating layers are difficult to distribute evenly on the surface of the positive electrode active material. Island-like coatings may form in some places on the surface of the positive electrode active material, resulting in an excessively thick coating layer, while other places have no coating layer. The areas without coating layer cannot play the role of isolating the electrolyte. Moreover, the presence of island-like coatings will affect the transport of lithium ions, resulting in poor improvement in battery life.
[0053] The lithium secondary battery of this application controls the standard deviation of the mass percentage of the coating elements (any one of Si, P, S, B, F, Cu, Zn, Y, and Zr) at different positions on the surface of the positive electrode active material, i.e., the coating layer, to be 0.1%-0.25%, and the average mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr in n regions to be 0.1%-0.4%. This ensures that the elements in the coating layer are uniformly distributed on the body surface, preventing the coating layer on the surface of the positive electrode active material from being too thick and affecting lithium-ion transport, thus giving the lithium secondary battery excellent cycle storage performance. It also allows the coating layer to effectively isolate the electrolyte, effectively protecting the positive electrode active material, thereby significantly improving the cycle life of the lithium secondary battery containing it.
[0054] The lithium secondary battery disclosed in this application can be used in electrical devices that use batteries as a power source or in various energy storage systems that use batteries as energy storage elements. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.
[0055] The first aspect of this application discloses a lithium secondary battery, which includes a positive electrode, an electrolyte, and a negative electrode.
[0056] The positive electrode sheet includes a positive electrode active material, which includes a body and a coating layer formed on at least a portion of the surface of the body. The coating layer includes one or more elements selected from Si, P, S, B, F, Cu, Zn, Y, and Zr.
[0057] The surface of the positive electrode active material has n regions, where n is greater than or equal to 3. The standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.25%, and the average mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.4%.
[0058] The lithium secondary battery of this application controls the standard deviation of the mass percentage of the coating elements at different positions on the surface of the positive electrode active material (i.e., the coating layer) to be 0.1%-0.25%, and the average mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in n regions to be 0.1%-0.4%. This ensures that the elements of the coating layer are uniformly distributed on the surface of the body, which can reduce the situation where the coating material is too thick on the body and forms island-like coatings, thereby reducing the impact of excessive coating thickness on lithium-ion transport and giving the lithium secondary battery excellent cycle storage performance. It can also reduce the situation where some positions on the body are not covered by the coating layer, so that the coating layer can fully isolate the electrolyte and effectively protect the positive electrode active material, thereby significantly improving the cycle life of the lithium secondary battery containing it.
[0059] The oxides or inorganic salts formed by the coating elements (Si, P, S, B, F, Cu, Zn, Y, Zr) not only have high chemical stability, which can protect the positive electrode active material from corrosion by HF in the electrolyte, but also have lower electrochemical activity, reducing side reactions of the electrolyte on the surface of the positive electrode material.
[0060] As an example, the standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions can be 0.1%-0.25%, 0.15%-0.23%, 0.16%-0.2%, 0.17%-0.18%, etc. In some other embodiments of this application, n=5, and the standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.25%.
[0061] Understandably, the larger n is, the more accurately the standard deviation of the mass percentage of any one of the elements Si, P, S, B, F, Cu, Zn, Y, and Zr in the n regions can characterize the distribution of elements in the coating layer on the bulk surface. For example, n can be 3-1000, 10-900, 50-800, 100-700, 200-600, 300-500, etc.
[0062] Understandably, standard deviation, also known as standard deviation, is a measure of how much a set of values (in this application, it refers to the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in n regions) disperses from the average value. A larger standard deviation indicates that most values differ significantly from the average; a smaller standard deviation indicates that these values are closer to the average. In this application, the smaller the standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions, the more uniform the distribution of the coating element (any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements, hereinafter referred to as coating element) on the bulk surface.
[0063] The formula for calculating the standard deviation σ of the mass percentage of the coated elements in n regions is: σ=[Σ(w i -w0) 2 / n] 1 / 2 Where i = 1, 2, ..., n, w i Let σ represent the mass percentage of the coating element in the i-th region out of n regions, and w0 represent the average mass percentage of the coating element on the surface of the coating layer. Furthermore, Σ represents summation; for example, when n = 4, σ = [Σ((w1 - w0)] 2 +(w2-w0) 2 +(w3-w0) 2 +(w4-w0) 2 ) / 4] 1 / 2 .
[0064] Furthermore, it is understood that any two regions among the n regions on the surface of the positive electrode active material may partially overlap or not. The region used to calculate the standard deviation may or may not use all regions on the surface of the positive electrode active material particles; as long as the regions do not completely overlap, they are within the scope of protection of this application. Moreover, regardless of whether n takes any number greater than or equal to 3, as long as the standard deviation calculated from a specific value of n falls within the range of this application, it should fall within the scope of protection of this application.
[0065] It is understood that in the embodiments of this application, the coating element exists in the coating layer in the form of an inorganic substance, such as an oxide or inorganic salt of the corresponding element.
[0066] It is understood that "the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in n regions" has a well-known meaning in the art and can be determined using instruments and methods well-known in the art. For example, it can be obtained by the following method:
[0067] SEM-EDS elemental two-dimensional surface distribution test:
[0068] Testing instruments: Hitachi SU8600 scanning electron microscope, Oxford Instruments EDS
[0069] Sample preparation steps: Place the target powder sample in an agate mortar, add a small amount of anhydrous ethanol, and grind thoroughly for 10-15 minutes to form a uniform suspension. Use an ultrasonic disperser (power ≥100W) to sonicate for 5-8 minutes to eliminate powder agglomeration. Select a 12mm diameter circular conductive adhesive (such as carbon tape) as the sample stage, ensuring its surface is smooth and wrinkle-free. Use a pipette to drop 10-15μL of the dispersed suspension into the center of the conductive adhesive, and allow it to air dry naturally or bake under an infrared lamp (50℃) for 3 minutes.
[0070] Test parameters: Accelerating voltage: 10kV, working distance: 8-15mm, beam current intensity: 10-30nA, magnification: 20k, detector: Si(Li)EDS detector, energy resolution ≤135eV.
[0071] Data processing:
[0072] Use complementary software (such as INCA or Aztec) to reconstruct the elemental surface distribution map, and then overlay the BSE image to generate a composite spectrum. When shooting SEM-EDS, the selected samples must be five adjacent samples. The sample selection steps are as follows: 1. First, select the densely packed area of samples under a 200x lens; 2. After selecting the area, do not move the lens position. Magnify to 2000-3000x, select the particle at the very center of the field of view as the central sample, and then select the four particles above, below, to the left, and to the right of the central sample as the other four SEM-EDS samples. The sampling area should be no less than 4μm. 2 The mass percentage of the coated elements in each region was calculated using the ZAF correction algorithm (atomic number-absorption-fluorescence correction).
[0073] The formula for calculating the standard deviation σ of the mass percentage of the coated elements in the n regions is: σ=[Σ(w i -w0) 2 / n] 1 / 2 Where i = 1, 2, ..., n, w i w0 represents the mass percentage of the coating element in the i-th region out of n regions, and w0 represents the average mass percentage of the coating element on the surface of the coating layer.
[0074] The formula for calculating the average mass percentage of the coated elements in n regions is w0 = (w1 + w2 + ... + w n ) / n.
[0075] It is understandable that when the coating layer on the surface of the host is uneven, some areas of the host surface may have excessively thick coating (such as island-shaped coating), while other areas may have excessively thin coating or even no coating. In this case, when sampling, if an island-shaped distribution is sampled, the average mass percentage of the coating element in the n regions may be within the range, but the mass percentage of the coating element in the region corresponding to the island-shaped coating will be too large, resulting in a larger standard deviation of the mass percentage of the coating element in the n regions, which is outside the range defined in this application. If no island-shaped coating is sampled, the coating layer is too thin, and the standard deviation of the mass percentage of the coating element in the n regions may be small, but the average mass percentage of the coating element in the n regions will be small, which is outside the range defined in this application.
[0076] In some embodiments of this application, the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in a single region is 0.1%-1%. For example, the mass percentage of the coating element in a single region can be 0.2%-0.9%, 0.3%-0.8%, 0.4%-0.7%, 0.5%-0.6%, etc. By controlling the mass percentage of the coating element in a single region within the above range, the coating layer can effectively isolate the positive electrode active material and the electrolyte, and the coating element in the coating layer will not be too large and affect the transport of lithium ions, thereby significantly improving the cycle life of the lithium secondary battery.
[0077] In some embodiments of this application, the volume average particle size Dv50 of the positive electrode active material is 3μm-10μm. For example, the volume average particle size Dv50 of the positive electrode active material can be 3μm-9.9μm, 4μm-9μm, 5μm-8μm, 6μm-7μm, etc. Controlling the volume average particle size Dv50 of the positive electrode active material within the above range can reduce the lengthening of the lithium-ion transport path caused by excessively large particle size of the positive electrode active material, thus enabling the lithium secondary battery to have excellent rate performance. It can also reduce the increase in contact area with the electrolyte caused by excessively small particle size of the positive electrode active material, thereby reducing the probability of side reactions between the positive electrode active material and the electrolyte, and thus significantly improving the cycle life of the lithium secondary battery.
[0078] It can be understood that "the volume average particle size Dv50 of the positive electrode active material" refers to the particle size corresponding to a cumulative volume distribution percentage of 50%, which can be measured using instruments and methods known in the art, such as referring to the standard GB / T19077-2016 and using a laser particle size analyzer (e.g., Malvern Master Size 3000).
[0079] In some embodiments of this application, the thickness of the coating layer is 2nm-10nm. For example, the thickness of the coating layer can be 2nm-9.9nm, 3nm-9nm, 4nm-8nm, 5nm-7nm, etc. Controlling the thickness of the coating layer within the above range ensures that the coating layer is sufficient to isolate the positive electrode active material and the electrolyte, and the coating elements are not excessive, which would affect the transport of lithium ions, thereby further improving the cycle life of the lithium secondary battery.
[0080] It is understood that the "thickness of the coating layer" is a well-known definition in the art and can be measured using methods known in the art, such as the following methods:
[0081] 1. Take the positive electrode active material and disperse the particles in a solvent (water is acceptable) using an ultrasonic disperser. Then, dry the dispersed particles in a spray dryer to form a powder. Next, place the powder in a vacuum drying oven to further remove the solvent from the particle surface. Finally, uniformly disperse the dried particles on a copper mesh or other support coated with a thin carbon or silicon oxide film, and fix the sample support under vacuum. 2. After the instrument preheats, adjust the electron beam focus and intensity to ensure a stable and uniform beam. Insert the sample into the TEM sample chamber and position it within the electron beam path by moving and tilting the sample stage. Select bright-field or dark-field imaging mode and adjust the current of the objective lens, intermediate lens, and projector lens to optimize the imaging effect. Acquire images through a fluorescent screen or imaging device and record the imaging parameters and sample information. Finally, analyze the acquired images, extract useful information, and properly preserve the data and sample. The thickness of the coating layer can then be measured using TEM images.
[0082] In some embodiments of this application, the body includes Li 1+x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2 (lithium-rich layered oxide), Li a Ni 0.5-x2 Mn 1.5-y2 M2 x2+y2 O4 (spinel-type positive electrode active material), LiMn 2-x3 M3 x3 O4 (lithium manganese oxide materials), LiNi x4 Co y4 Mn z4 M4 (1-x4-y4-z4) One or more of O2 (lithium nickel cobalt manganese oxide),
[0083] Wherein, M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr, M2 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr, 0.9≤a≤1.1, -0.2≤x2≤0.2, -0.02≤y2≤0.3, x2+y2≥0, 0<x3≤0.5, M3 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr, 0<x4≤1, 0<y4≤1, 0≤z4<1, M4 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr.
[0084] As examples, x1 may be 0.1-0.99, 0.2-0.9, 0.3-0.8, 0.4-0.7, 0.5-0.6, etc.; y1 may be 0.5-0.99, 0.6-0.9, 0.7-0.8, etc.; z1 may be 0.1-0.49, 0.2-0.4, 0.3-0.4, etc.; a may be 0.9-1.09, 0.95-1.05, 1-1.02, etc.; x2 may be -0.2-0.19, -0.15-0.15, -0.1-0.1, 0-0.05, etc.; y2 may be -0.02-0.29, 0-0.25, 0.1-0.2, etc.; x2+y2 may be 0-0.5, 0.1-0.4, 0.2-0.3, etc.; x3 may be 0.1-0.49, 0.2-0.4, 0.3-0.35, etc.; x4 may be 0.1-0.99, 0.2-0.9, 0.3-0.8, 0.4-0.7, 0.5-0.6, etc.; y4 may be 0.1-0.99, 0.2-0.9, 0.3-0.8, 0.4-0.7, 0.5-0.6, etc.; z4 may be 0.1-0.99, 0.2-0.9, 0.3-0.8, 0.4-0.7, 0.5-0.6, etc.
[0085] Specifically, the bulk of the above positive electrode active material is prone to side reactions with the electrolyte during the cycle of a lithium secondary battery, especially under high voltage. For the bulk represented by the above chemical formula, the present application provides a coating layer on the surface thereof and controls the standard deviation of the mass proportion of the coating elements, so that the elements of the coating layer are uniformly distributed on the surface of the bulk, the coating layer can sufficiently isolate the electrolyte, and can effectively protect the positive electrode active material, thereby significantly improving the cycle life of the lithium secondary battery containing the same.
[0086] In other embodiments of the present application, the bulk includes Li 1+x1 Mn y1M1 z1 Q (1-x1-y1-z1) O2 (lithium-rich layered oxide), wherein M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, and Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, Cr. A lithium-rich layered oxide (LLOs) cathode material requires a high charging cut-off voltage to activate the anion O 2- , so that most lithium ions are deintercalated to deliver higher capacity. However, the activated O 2- anion has strong oxidation reactivity, which aggravates the side reaction of oxidative decomposition of the electrolyte, leading to rapid attenuation of battery storage and cycle life. For the above bulk material, the present application provides a coating layer and controls the standard deviation of the mass proportion of the coating element, which can more effectively protect the cathode active material, thereby further improving the cycle life of a lithium secondary battery containing the same.
[0087] However, the present application is not limited to these materials, and other conventional materials that can be used as battery cathode active materials may also be used. These cathode active materials may be used alone or in combination of two or more. Among them, examples of the lithium transition metal oxide may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (may also be abbreviated as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (may also be abbreviated as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (may also be abbreviated as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (may also be abbreviated as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (may also be abbreviated as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2)) and modified compounds thereof, and the like.
[0088] In some embodiments of this application, the positive electrode active material body may also be a positive electrode active material known in the art for lithium-ion batteries.
[0089] As an example, the cathode active material body may also include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, and lithium iron manganese phosphate and carbon composites. The modified compounds of the above materials may be for doping modification and / or surface coating modification of the materials.
[0090] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before material addition. After charge-discharge cycles, the molar Li content changes when the positive electrode active material is applied to the battery system.
[0091] In the examples of positive electrode active materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.
[0092] In a second aspect, this application proposes a positive electrode active material, comprising a body and a coating layer formed on at least a portion of the surface of the body. The coating layer comprises one or more of Si, P, S, B, F, Cu, Zn, Y, and Zr elements. The surface of the positive electrode active material has n regions, where n is greater than or equal to 3. The standard deviation of the mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.25%, and the average mass percentage of any one of Si, P, S, B, F, Cu, Zn, Y, and Zr elements in the n regions is 0.1%-0.4%.
[0093] Therefore, the positive electrode active material proposed in this application controls the standard deviation of the mass percentage of the coating elements at different positions on the surface of the positive electrode active material, i.e., the coating layer, to be 0.1%-0.25%, so that the coating layer is uniformly coated on the body surface, which can effectively protect the positive electrode active material and thus significantly improve the cycle life of the lithium secondary battery containing it.
[0094] It is understood that the other additional technical features of the positive electrode active material proposed in this application have been described in detail above and will not be repeated here.
[0095] In a third aspect of this application, a method for preparing the positive electrode active material described in the second aspect is provided, the method comprising:
[0096] S1. Dissolve a soluble compound or a soluble polymer in water to form a solution, wherein the soluble compound includes one or more of the following elements: Si, P, S, B, F, Cu, Zn, Y, and Zr.
[0097] This step first involves dissolving the raw materials (soluble compounds) and polymers of the coating layer in water to form a homogeneous and stable solution. The soluble compounds provide the coating elements, while the soluble polymers can regulate the uniformity of the coating layer on the substrate surface. This is a liquid-phase coating method, where the substrate is placed in a liquid coating material. Compared to solid-phase coating, liquid-phase coating is a method that can coat the positive electrode active material more uniformly and densely, and it is more effective in preventing direct contact between the electrolyte and the positive electrode active material.
[0098] In some embodiments of this application, the soluble compounds include Na₂SiO₃, Li₂SiO₃, K₂SiO₃, H₄SiO₄, LiH₂PO₃, NaH₂PO₃, KH₂PO₃, Li₂HPO₃, Na₂HPO₃, K₂HPO₃, (NH₄)₃PO₄, NaF, KF, NH₄F, NaBF₄, H₂SiF₆, Na₂SO₄, K₂SO₄, (NH₄)₂SO₄, Na₂SO₃, K₂SO₃, Na₂S₂O₃, and Li₂B₂O₃. One or more of the following: 4O7, Li2B4O7·10H2O, H2BO3, CuSO4, Cu(NO3)2, ZnSO4, Zn(NO3)2, Y(NO3)2, YCl3, Zr(SO4)2. The above soluble compounds are readily soluble in water and can form a homogeneous solution. They also include one or more of the following elements: Si, P, S, B, F, Cu, Zn, Y, and Zr, which facilitates the formation of a uniform coating layer on the surface of the host when the host is placed therein.
[0099] In some embodiments of this application, the average molecular weight of the soluble polymer is 500-100,000. For example, the average molecular weight of the soluble polymer can be 500-90,000, 1,000-80,000, 2,000-70,000, 3,000-60,000, 10,000-50,000, 20,000-40,000, etc. By controlling the average molecular weight of the soluble polymer within the above range, the soluble polymer can form a network structure on the surface of the positive electrode active material, inhibiting the flow of the surface liquid film and slowing down the mass transfer of the soluble compound. In addition, the soluble polymer with the above molecular weight may act as a surfactant, adsorbing on the crystal surface formed by the soluble compound, directly inhibiting the disordered growth of the soluble compound crystals, reducing the formation of island-like coatings on the positive electrode active material, and facilitating the formation of a uniform coating layer on the surface of the material, thereby improving the cycle life of the lithium secondary battery containing the positive electrode active material.
[0100] It is understood that the average molecular weight of soluble polymers is a well-known definition in the art and can be determined using methods known in the art, such as the following methods:
[0101] Gel permeation chromatography (GPC): Sample preparation: Weigh 5–10 mg of sample, dissolve in the corresponding solvent (e.g., THF to dissolve PS), sonicate for 10 minutes, and filter through a 0.45 μm filter membrane. Instrument configuration: Column: 3 gel columns in series (e.g., Agilent PLgelMIXED-B), column temperature 35℃. Mobile phase: Tetrahydrofuran (flow rate 1.0 mL / min). Detector: Differential refractive index detector + multi-angle laser light scattering detector. Calibration and determination: Establish a standard curve (retention time vs. logarithm of molecular weight) using narrow-distribution polystyrene standards. Record the chromatogram after injection; the software automatically calculates the average molecular weight.
[0102] In some embodiments of this application, the soluble polymer includes one or more of polyacrylic acid, sodium polyacrylate, polymethacrylic acid, polyethyleneimine, polyacrylamide, polyvinyl alcohol, polymethylacrylamide, polyallylamine, polydiallylamine, polyethylene glycol, polyvinyl acetate, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, and sodium chondroitin sulfate A. These soluble polymers are readily soluble in water, forming a homogeneous solution. During the liquid-phase preparation of the coating layer, these polymers can form a network structure on the surface of the positive electrode active material, inhibiting the flow of the surface liquid film and slowing down the mass transfer of the soluble compound. Furthermore, these soluble polymers may act as surfactants, adsorbing onto the crystal surface formed by the soluble compound, directly inhibiting the disordered growth of the soluble compound crystals, reducing the formation of island-like coatings on the positive electrode active material, and facilitating the formation of a uniform coating layer on the surface of the material, thereby improving the cycle life of the lithium secondary battery containing this positive electrode active material.
[0103] In some embodiments of this application, the mass ratio of the soluble compound, the soluble polymer, and water is (1-100):(1-30):100. For example, the mass ratio of the three can be (1-90):(1-30):100, (10-80):(1-30):100, (50-600):(1-30):100, (1-100):(1-25):100, (1-100):(10-20):100, etc. Controlling the ratio of the soluble compound, the soluble polymer, and water within the above range can reduce the excessive porosity of the coating layer caused by excessive soluble polymer (because it can...). The soluble polymer reacts with oxygen during the subsequent calcination stage to generate gases such as carbon dioxide, carbon monoxide, and water. This reduces the insignificant control over the uniformity of the coating layer caused by insufficient soluble polymer, as well as the excessively thin coating layer caused by insufficient soluble compounds, and the excessively thick coating layer caused by excessive soluble compounds. This results in a coating layer of moderate and uniform thickness on the surface of the substrate, further improving the cycle life of lithium secondary batteries containing this positive electrode active material.
[0104] S2. Immerse the main body in the solution to separate the solid and liquid, and obtain a solid.
[0105] This step involves immersing the substrate in a solution for liquid-phase coating. During this process, the soluble polymers in the solution can regulate the distribution of soluble compounds on its surface, ensuring that they are evenly distributed on the surface.
[0106] In some embodiments of this application, the soaking time is 5 min-30 min, for example, the soaking time can be 5 min-29 min, 10 min-25 min, 15 min-20 min, etc. Therefore, by controlling the soaking time within the above range, the uneven distribution of soluble compounds on the substrate caused by too short a soaking time can be reduced, and the occurrence of some parts of the substrate not being coated can be reduced. It can also reduce the occurrence of water entering the interior of the substrate and damaging the structure of the substrate caused by too long a soaking time, so as to obtain a positive electrode active material with uniform coating layer and strong stability, and improve the cycle storage life of lithium secondary batteries containing the positive electrode active material.
[0107] In some embodiments of this application, the solid-liquid separation includes one or more of centrifugation, vacuum filtration, and pressure filtration. Using the above separation methods, the solution can be uniformly distributed on the surface of the positive electrode active material, reducing the probability of droplets on the surface of the material, thereby obtaining a positive electrode active material with a uniformly distributed coating and strong stability, and improving the cycle life of lithium secondary batteries containing this positive electrode active material.
[0108] In some embodiments of this application, the solution after solid-liquid separation can be recycled for the next liquid phase coating, reducing the loss of coating raw materials.
[0109] In some embodiments of this application, the calcination temperature is 400℃-700℃. For example, the calcination temperature can be 400℃-690℃, 450℃-650℃, 500℃-600℃, etc. Controlling the calcination temperature within the above range, in an oxygen-containing atmosphere (such as an air atmosphere or an oxygen atmosphere), allows the water and soluble polymers in the solution coating the surface of the substrate to fully volatilize and decompose, thereby forming a uniform coating layer on the substrate and improving the cycle life of the lithium secondary battery containing the positive electrode active material.
[0110] In summary, the method for preparing the positive electrode active material proposed in this application involves adding a soluble polymer during the liquid-phase coating process. The soluble compounds in the solution begin to nucleate and crystallize upon water evaporation, and then grow. If left uncontrolled, the crystal grains formed on the substrate surface by the soluble compounds will be very large, failing to achieve a dense and uniform coating of the positive electrode material. The principle behind the addition of soluble polymers to inhibit the growth of soluble compound crystals in inorganic components is as follows: On one hand, the soluble polymers can form a network structure on the substrate surface of the positive electrode active material, inhibiting the flow of the surface liquid film and slowing down the mass transfer of the soluble compounds; on the other hand, the soluble polymers may act as surfactants, adsorbing onto the surface of the crystals formed by the soluble compounds, directly inhibiting the disordered growth of the soluble compound crystals. Therefore, after sintering, a dense and uniform coating layer can be obtained on the substrate surface, thereby improving the cycle life of lithium secondary batteries containing this positive electrode active material.
[0111] Typically, a battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active metal ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0112] In some embodiments of this application, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes the aforementioned irreversible positive electrode additive.
[0113] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0114] In some embodiments of this application, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0115] In some embodiments of this application, the positive electrode active material layer may optionally include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0116] In some embodiments of this application, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0117] In some embodiments of this application, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder, positive irreversible additive and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0118] In some embodiments of this application, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector.
[0119] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0120] In some embodiments of this application, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0121] In some embodiments of this application, the negative electrode active material may be any negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, and lithium titanate, etc. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0122] In some embodiments of this application, the negative electrode active material layer may optionally include a binder. The binder may be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0123] In some embodiments of this application, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0124] In some embodiments of this application, the negative electrode active material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0125] In some embodiments of this application, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0126] This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or completely solid.
[0127] In some embodiments of this application, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0128] In some embodiments of this application, when the battery is a lithium-ion battery, the electrolyte salt may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, or lithium tetrafluorooxalate phosphate. In other embodiments of this application, the lithium salt includes one or more of LiPF6 and LiFSI.
[0129] In some embodiments of this application, the solvent may further include one or more of the following: chain carbonates, cyclic carbonates, carboxylic acid esters, and ethers. The solvent may include one or more of the following: ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone, diethyl sulfone, tetrahydrofuran, dimethyl ether, diethyl ether, and ethylene glycol dimethyl ether.
[0130] In some embodiments of this application, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0131] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0132] In some embodiments of this application, the material of the separator may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0133] The secondary batteries of this application include single-cell battery forms, battery module forms, and battery pack forms. The following description, with appropriate reference to the accompanying drawings, will illustrate the single-cell battery, battery module, and battery pack of this application.
[0134] In some embodiments of this application, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly by a winding process or a stacking process.
[0135] In some embodiments of this application, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the aforementioned electrode assembly and electrolyte.
[0136] In some embodiments of this application, the outer packaging of the battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0137] It is understood that the lithium secondary battery mentioned above in this application is a single battery cell.
[0138] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 Here is a square-structured battery cell 1 as an example.
[0139] In some embodiments of this application, reference is made to Figure 2 The outer packaging may include a housing 11 and a cover plate 13. The housing 11 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 11 has an opening communicating with the receiving cavity, and the cover plate 13 can be placed over the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 12 by a winding process or a stacking process. The electrode assembly 12 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 12. The number of electrode assemblies 12 contained in a single battery cell 1 can be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0140] In some embodiments of this application, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0141] Figure 3 This is battery module 2 as an example. (See reference...) Figure 3 In battery module 2, multiple battery cells 1 can be arranged sequentially along the length of battery module 2. Of course, they can also be arranged in any other way. Furthermore, these multiple battery cells 1 can be fixed in place using fasteners.
[0142] Optionally, the battery module 2 may also include a housing with a receiving space in which multiple battery cells 1 are received.
[0143] In some embodiments of this application, the battery modules described above can also be assembled into a battery pack. The number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0144] Figure 4 and Figure 5 This is battery pack 3 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 3 may include a battery box and multiple battery modules 2 disposed within the battery box. The battery box includes an upper box 31 and a lower box 32, with the upper box 31 covering the lower box 32 to form a closed space for accommodating the battery modules 2. The multiple battery modules 2 can be arranged in any manner within the battery box.
[0145] In addition, this application also provides an electrical device, which includes the lithium secondary battery provided in the first aspect of this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0146] As the electrical equipment, battery cells, battery modules, or battery packs can be selected according to their usage requirements.
[0147] Figure 6 This is an example of an electrical device. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0148] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0149] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0150] Example 1
[0151] 1. Preparation of positive electrode sheet
[0152] Preparation of positive electrode active materials:
[0153] At room temperature, lithium dihydrogen phosphate was first dissolved in a polyacrylic acid solution (the average molecular weight of polyacrylic acid is 2000) to obtain solution A, with a mass ratio of lithium dihydrogen phosphate, polyacrylic acid, and water of 5:5:100; then, the positive electrode active material (lithium-rich layered oxide, chemical formula Li) was taken. 1.16 Ni 0.168 Co 0.084 Mn 0.588 O2) was added to 1050g of solution A and stirred until homogeneous to obtain suspension B. The bulk material was immersed in solution A for 10min. The suspension was centrifuged, filtered, and dried to obtain a positive electrode active material uniformly coated with lithium dihydrogen phosphate and polyacrylic acid. The separated solution could be recycled. Finally, the positive electrode active material uniformly coated with lithium dihydrogen phosphate and polyacrylic acid was sintered in air at 700℃ for 3h to obtain Li3PO4 coated positive electrode active material.
[0154] According to standard GB / T 19077-2016, the volume average particle size Dv50 of the positive electrode active material was 7 μm and the thickness of the coating layer was 5 nm as measured by transmission electron microscopy.
[0155] The prepared positive electrode active material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were dissolved in N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5. After thorough mixing, a positive electrode slurry was obtained. The positive electrode slurry was then uniformly coated onto a positive electrode current collector, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The areal density of a single layer of positive electrode active material was 350 mg / 1540.25 mm². 2 .
[0156] 2. Preparation of negative electrode sheet
[0157] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) were mixed in a mass ratio of 96.3:0.7:1.2:1.8. Deionized water was added and the mixture was stirred thoroughly to form a negative electrode slurry. The negative electrode slurry was uniformly coated onto one surface of the negative electrode current collector copper foil. After drying and cold pressing, the negative electrode sheet was obtained. The areal density of a single layer of negative electrode active material was 142 mg / 1540.25 mm². 2 .
[0158] 3. Preparation of electrolyte
[0159] Ethylene carbonate (EC), diethyl carbonate, and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0160] 4. Separating membrane
[0161] A polyethylene film with a thickness of 13 μm was used as the separator.
[0162] 5. Preparation of lithium secondary batteries
[0163] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide insulation. The resulting bare cell is then wound together, tabs are welded onto it, and the cell is placed in an aluminum casing. It is then baked at 80°C to remove moisture, followed by the injection of electrolyte and sealing, resulting in a non-charged battery. This non-charged battery then undergoes a series of processes including settling, hot and cold pressing, formation, shaping, and capacity testing to obtain a lithium-ion battery.
[0164] The preparation methods of lithium-ion batteries in Examples 2-10 and Comparative Examples 1-2 are the same as those in Example 1, except that the process parameters for preparing the positive electrode active material are different, as shown in Table 1.
[0165] In Example 2, lithium dihydrogen phosphate was replaced with Na2SiO3; in Example 3, lithium dihydrogen phosphate was replaced with NaF; in Example 4, lithium dihydrogen phosphate was replaced with ZnSO4; and in Examples 5-10, lithium dihydrogen phosphate was used to provide the coating element P. Comparative Example 1 only used the bulk material from Example 1 as the positive electrode active material. In Comparative Example 1, there was no coating element, and the bulk material may also contain a small amount of P impurities. Therefore, the average mass percentage of the coating element was not 0.
[0166] Table 1
[0167]
[0168] 1. Determination of the mass percentage and standard deviation of the coating elements in five regions on the surface of the positive electrode active material:
[0169] Testing instruments: Hitachi SU8600 scanning electron microscope, Oxford Instruments EDS.
[0170] Sample preparation steps: Place the target powder sample in an agate mortar, add a small amount of anhydrous ethanol, and grind thoroughly for 10-15 minutes to form a uniform suspension. Use an ultrasonic disperser (power ≥100W) to sonicate for 5-8 minutes to eliminate powder agglomeration. Select a 12mm diameter circular conductive adhesive (such as carbon tape) as the sample stage, ensuring its surface is smooth and wrinkle-free. Use a pipette to drop 10-15μL of the dispersed suspension into the center of the conductive adhesive, and allow it to air dry naturally or bake under an infrared lamp (50℃) for 3 minutes.
[0171] Test parameters: Accelerating voltage: 10kV, working distance: 8-15mm, beam current intensity: 10-30nA, magnification: 20k, detector: Si(Li)EDS detector, energy resolution ≤135eV.
[0172] Data processing:
[0173] Use complementary software (such as INCA or Aztec) to reconstruct the elemental surface distribution map, and then overlay the BSE image to generate a composite spectrum. When shooting SEM-EDS, the selected samples must be five adjacent samples. The sample selection steps are as follows: 1. First, select the densely packed area of samples under a 200x lens; 2. After selecting the area, do not move the lens position. Magnify to 2000-3000x, select the particle at the very center of the field of view as the central sample, and then select the four particles above, below, to the left, and to the right of the central sample as the other four SEM-EDS samples. The sampling area should be no less than 4μm. 2 The mass percentage of the coated elements in each region was calculated using the ZAF correction algorithm (atomic number-absorption-fluorescence correction).
[0174] The formula for calculating the standard deviation σ of the mass percentage of the coating elements in the 5 regions is: σ=[Σ(w i -w0) 2 / 5] 1 / 2 Where i = 1, 2…5, w i w0 represents the mass percentage of the coating element in the i-th region among the five regions, and w0 represents the average mass percentage of the coating element on the surface of the coating layer.
[0175] The formula for calculating the average mass percentage of the coating elements in the five regions is w0 = (w1 + w2 + ... + w5) / 5.
[0176] 2. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) of the positive electrode active material:
[0177] The positive electrode active materials obtained in Examples 1 and 2, and Comparative Examples 1 and 2, were subjected to scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) to obtain... Figures 7-14 ;
[0178] EDS and SEM images of the positive electrode active material of Comparative Example 1 are shown below. Figure 7 and Figure 8 As shown, Comparative Example 1 was not coated in any way, and the surface of the positive electrode active material was smooth. EDS analysis showed that the phosphorus content on the surface of the positive electrode active material was basically 0.
[0179] EDS and SEM images of two sites of the positive electrode active material in Comparative Example 2 are shown below. Figure 9 and Figure 10 As shown, it can be seen that Figure 9 The positive electrode active material showed some island-like coatings, and EDS analysis revealed uneven distribution of phosphorus. Figure 9 The measured mass percentage of phosphorus in the sample was 3.86%, while Figure 10 Phosphorus content is very low, accounting for only 0.19% of total mass. Figure 10 In some cases, the positive electrode active material lacks a coating layer. Figure 9 and Figure 10 It can be seen that the coating layer on the surface of the positive electrode active material in Comparative Example 2 is not uniform.
[0180] EDS and SEM images of the positive electrode active material in Example 1 are shown below. Figure 11 and Figure 12 As shown, the phosphorus element on the surface of the positive electrode active material prepared in Example 1 is uniformly distributed, with a mass ratio of 0.32%, and a uniform coating layer is formed on the surface of the substrate.
[0181] EDS and SEM images of the positive electrode active material in Example 2 are shown below. Figure 13 and Figure 14 As shown, the silicon element on the surface of the positive electrode active material prepared in Example 2 is uniformly distributed, with a mass ratio of silicon element of 0.54%, and a uniform coating layer is formed on the surface of the substrate.
[0182] The capacity, cycle life, and storage life of the batteries in Examples 1-10 and Comparative Examples 1-2 were characterized, and the characterization results are shown in Table 2.
[0183] 1. Capacity Test: At 25℃, the prepared lithium secondary battery was charged at a constant current of 0.1C until the voltage reached 4.5V. Once the voltage reached 4.5V, the charging mode was switched to constant voltage charging mode, maintaining the voltage at 4.5V until the charging current dropped to 0.05C. The battery was then discharged at a constant current of 0.33C until the voltage dropped to 2.0V. The discharge capacity at this point was recorded as the battery's capacity.
[0184] 2. Cycle Life Test: At 25℃, the prepared lithium secondary battery was charged at a constant current of 0.33C until the voltage reached 4.5V. Once the voltage reached 4.5V, the charging mode was switched to constant voltage charging mode, maintaining the voltage at 4.5V until the charging current dropped to 0.05C. The battery was then discharged at a constant current of 0.33C until the voltage dropped to 2.0V. The discharge capacity at this point was recorded, which is the battery capacity C0. The lithium secondary battery was continued to undergo cycle charge-discharge testing using the above method, and the discharge capacity after each cycle was recorded. After 100 cycles, the capacity was C100, indicating the capacity retention rate.
[0185] =C100 / C0×100%.
[0186] 3. Storage performance test: The battery is subjected to a standard charge and discharge test at 25℃.
[0187] (1) Initial capacity test (C0)
[0188] Constant current discharge (DC): Discharge to 2.0V with a current of 0.33C.
[0189] Low current discharge (DC): Discharge to 2.0V with a current of 0.05C.
[0190] Constant current charging (CC): Charges to 4.5V at a current of 0.33C.
[0191] Constant voltage charging (CV): Maintain a voltage of 4.5V until the charging current drops to 0.05C.
[0192] Constant current discharge (DC): Discharge to 2.0V with a current of 0.33C.
[0193] Low current discharge (DC): Discharge to 2.0V with a current of 0.05C.
[0194] Record the initial discharge capacity C0.
[0195] (2) High-temperature storage
[0196] After fully charging the battery, place it in a constant temperature chamber at 50℃ for 2, 4, 6, 10, and 14 days respectively.
[0197] Remove the battery after each storage cycle.
[0198] (3) Post-storage capacity test (Cn)
[0199] After storage, the battery should be left to stand at 25°C for 2 hours to stabilize its condition.
[0200] Perform charge and discharge tests according to the initial capacity test procedure:
[0201] Constant current discharge (DC): Discharge to 2.0V with a current of 0.33C.
[0202] Low current discharge (DC): Discharge to 2.0V with a current of 0.05C.
[0203] Record the reversible discharge capacity Cn after each storage.
[0204] (4) Calculate the reversible capacity retention rate
[0205] Calculate the reversible capacity retention rate after storage for n days, where n is the number of storage days, and Cn / C0×100% is the reversible capacity retention rate after storage for n days. The results are shown in Table 2.
[0206] The high-temperature storage performance comparison graphs of lithium secondary batteries in Examples 1 and 2, and Comparative Examples 1 and 2 are shown in Figure 1. Figure 15 As shown, the lithium secondary battery containing the positive electrode active material prepared in the embodiments of this application has excellent storage life.
[0207] Table 2
[0208]
[0209] As shown in Table 2, in Examples 1-10 of this application, by simultaneously controlling the average value and standard deviation of the mass percentage of the coating elements, the elements of the coating layer are uniformly distributed on the surface of the substrate, which can effectively protect the positive electrode active material and thus significantly improve the cycle life of the lithium secondary battery containing it. Comparative Example 1 does not contain a coating layer, and the coating layer of Comparative Example 2 is unevenly coated, and the cycle life of the battery is significantly lower than that of Examples 1-10.
[0210] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A lithium secondary battery, characterized in that, The lithium secondary battery includes a positive electrode plate, an electrolyte and a negative electrode plate, The positive electrode plate comprises a positive electrode active material, and the positive electrode active material comprises a main body and a coating layer formed on at least part of the surface of the main body, the coating layer comprises one or more of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element, There are n regions on the surface of the positive electrode active material, n is greater than or equal to 3, the standard deviation of the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element in the n regions is 0.1%-0.25%, and the average value of the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element in the n regions is 0.1%-0.4%.
2. The lithium secondary battery according to claim 1, characterized in that, In a single region, the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element is 0.1%-1%; and / or, The thickness of the coating layer is 2nm-10nm.
3. The lithium secondary battery according to claim 1 or 2, characterized in that, The body includes Li 1+ x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, Li a Ni 0.5-x2 Mn 1.5-y2 M2 x2+y2 O4, LiMn 2-x3 M3 x3 O4、 LiNi x4 Co y4 Mn z4 M4 (1-x4-y4-z4) One or more of O2, Wherein, M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr, M2 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr, 0.9≤a≤1.1, -0.2≤x2≤0.2, -0.02≤y2≤0.3, x2+y2≥0, 0<x3≤0.5, M3 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr, 0<x4≤1, 0<y4≤1, 0≤z4<1, M4 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V and Cr.
4. The lithium secondary battery according to any one of claims 1-3, characterized in that, The main body includes Li 1+ x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, wherein M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, and Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, Cr.
5. A positive electrode active material, characterized in that, The positive electrode active material comprises a main body and a coating layer formed on at least part of the surface of the main body, the coating layer comprises one or more of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element, There are n regions on the surface of the positive electrode active material, n is greater than or equal to 3, the standard deviation of the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element in the n regions is 0.1%-0.25%, and the average value of the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element in the n regions is 0.1%-0.4%.
6. The positive electrode active material according to claim 5, characterized in that, In a single region, the mass proportion of any one of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element and Zr element is 0.1%-1%; and / or, The thickness of the coating layer is 2 nm to 10 nm; and / or, The body includes Li. 1+x1 Mn y1 M1 z1 Q (1-x1-y1-z1) O2, Li a Ni 0.5-x2 Mn 1.5-y2 M2 x2+y2 O4, LiMn 2-x3 M3 x3 O4, LiNi x4 Co y4 Mn z4 M4 (1-x4-y4-z4) One or more of O2, Wherein, M1 includes one or more of Ni and Co, 0<x1≤1, 0.5<y1≤1, 0≤z1<0.5, Q includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, M2 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, 0.9≤a≤1.1, -0.2≤x2≤0.2, -0.02≤y2≤0.3, x2+y2≥0, 0<x3≤0.5, M3 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr, 0<x4≤1, 0<y4≤1, 0≤z4<1, M4 includes one or more of Mg, Zn, Ti, Zr, W, Nb, Al, B, P, Mo, V, and Cr.
7. A method for preparing a positive electrode active material, characterized in that, comprises: dissolving a soluble compound and a soluble polymer in water to form a solution, wherein the soluble compound comprises one or more of Si element, P element, S element, B element, F element, Cu element, Zn element, Y element, and Zr element; immersing the bulk material in the solution, and performing solid-liquid separation to obtain a solid; calcining the solid in an oxygen-containing atmosphere to obtain a positive electrode active material.
8. The method according to claim 7, characterized in that, The soluble compound comprises one or more of Na₂SiO₃, Li₂SiO₃, K₂SiO₃, H₄SiO₄, LiH₂PO₃, NaH₂PO₃, KH₂PO₃, Li₂HPO₃, Na₂HPO₃, K₂HPO₃, (NH₄)₃PO₄, NaF, KF, NH₄F, NaBF₄, H₂SiF₆, Na₂SO₄, K₂SO₄, (NH₄)₂SO₄, Na₂SO₃, K₂SO₃, Na₂S₂O₃, Li₂B₄O₇, Li₂B₄O₇·10H₂O, H₃BO₃, CuSO₄, Cu(NO₃)₂, ZnSO₄, Zn(NO₃)₂, Y(NO₃)₂, YCl₃, and Zr(SO₄)₂; and / or, The average molecular weight of the soluble polymer is 500 to 100000; and / or, The soluble polymer comprises one or more of polyacrylic acid, sodium polyacrylate, polymethacrylic acid, polyethyleneimine, polyacrylamide, polyvinyl alcohol, polymethacrylamide, polyallylamine, polydiallylamine, polyethylene glycol, polyvinyl acetate, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, and chondroitin sulfate A sodium salt.
9. The method according to claim 7 or 8, characterized in that, The mass ratio of the soluble compound, the soluble polymer and water is (1-100):(1-30):100; and / or, The immersion time is 5 min to 30 min; and / or, The solid-liquid separation comprises one or more of centrifugation, suction filtration, and pressure filtration; and / or, The calcination temperature is 400°C to 700°C.
10. An electrical appliance, characterized in that, comprising the lithium secondary battery according to any one of claims 1 to 4.